A Model For Short-Range Planning And Monitoring Of Mining In Potassium Deposits Of Level Formation - F. L. Wilke (Society for Mining, Metallurgy & Exploration, 1979)
A model is presented to minimize the winning costs per shift within the different sections of a potassium mine by liner programming and to simulate the other areas to get all costs in order to comp re different production strategies. he model is based on a a given total layout of the underground mining which is considered to be fix during the planning period. Room-and-pillar mining is assumed to be used. Potassium extraction is done by drilling and blasting. Transportation of the raw material to sectional crushers is done by scoop-trams where it is crushed to coarse-grains which allow further transportation by conveyor belts to the hoisting shaft or to a bunker. When production is stopped, the continuously working factory is supplied by means of this bunker. Starting from a desired composition of the raw material the model has to keep the given total. demand of raw material per shift, to minimize the winning costs, to keep the capacity constraints of the equipment and to determine the planned output of production of the sections per shift. Costs of the areas which follow the extractions are added to extraction costs in order to allow a comparision of costs of several alternatives of production. Optimization in extraction and assignment of scoop-trams to sections is done by linear programming. The other areas of the mine are treated by simulation. The model output is a schedule of the calculated costs broken down into costs of processes, equipment, and kinds of costs. This proceeding enables to compare different ways of production.